Learning Difficulties of High School Students in Understanding the Material of Human Reproductive Systems Triggering Misconceptions - Naning Wahyuni; Hadi Suwono; Umie Lestari (Universitas Negeri Malang, 2019)
Abstract: Human Reproductive System is a basic concept in biological sciences that is related to daily life and interesting for high school students. Complicated learning materials make it difficult for students to construct their knowledge and understand the concepts. Survey research using a questionnaire was conducted to determine the causes of difficulties for high school students in understanding the Human Reproductive System concepts. Respondents were grade XII science students and two teachers. The data obtained were analyzed descriptively. The research findings indicate that students' difficulties are due to (1) the extensive usage of scientific terms, (2) abstract concepts, (3) monotone, and (4) inadequate sources of information. The implication of this result is that teachers are required to elaborate appropriate strategies and textbooks to lead students getting accurate knowledge. Key Words: learning difficulties, senior high school students, human reproductive system, teacher, textbook, misconception Abstrak: Sistem Reproduksi Manusia merupakan konsep dasar dalam ilmu biologi yang berkaitan de-ngan kehidupan sehari-hari dan menarik bagi siswa SMA untuk dipelajari. Namun, kompleksitas materi seringkali membuat siswa kesulitan dalam membangun struktur pengetahuan dan memahami konsep.  Penelitian survei dengan menggunakan instrumen kuesioner dilakukan untuk mengetahui penyebab kesulitan siswa SMA dalam mempelajari materi ini yang berpotensi memicu miskonsepsi. Responden adalah siswa kelas XII IPA dan guru. Data yang diperoleh dianalisis secara deskriptif. Temuan penelitian menunjukkan bahwa kesulitan siswa disebabkan karena: 1) terdapat istilah asing yang sulit dimengerti dan diingat, 2) beberapa sub konsep bersifat abstrak sehingga sulit dipahami dalam konteks nyata, 3) cara guru menyampaikan materi terlalu monoton dan tidak menarik, 4) sumber informasi yang kurang memadai. Implikasi dari penelitian ini adalah guru perlu mengembangkan strategi pembelajaran yang menarik dan memilih buku teks yang baik sehingga siswa memperoleh pengetahuan yang akurat. Kata kunci: kesulitan belajar, siswa SMA, sistem reproduksi manusia, guru, buku teks, miskonsepsi